Effect of Motivation to Learn and Environmental Factors on University Students’ Study Habits - Cao, Eldis Román; Alexander López Padrón; Yunia Tania Pérez Medinilla; Erisadanis Díaz Pérez; Antonio Clarencio Guzmán Ramírez (Journal of Education Culture and Society, 2026)
Aim. The objective of this cross-sectional study was to analyze the relationship between age, sex, study environment conditions, motivation to learn, and study habits among university students at the Technical University of Manabí, Ecuador. Methods. A descriptive-correlational study with predictive scope was conducted using a non-experimental, cross-sectional design. A self-report questionnaire was administered to assess study environment conditions, motivation to learn, and study habits to 273 university students between October 2023 and January 2024. Descriptive statistics, correlational analyses, and multiple linear regression were performed using IBM SPSS Statistics (version 27). Results. Descriptive analyses revealed high levels of motivation to learn, moderate levels of study habits, and comparatively lower levels of favorable environmental conditions for studying. Correlational analyses showed positive and significant associations between environmental conditions, motivation to learn, and study habits. The regression model explained 16% of the variance in study habits, identifying motivation to learn as the strongest predictor, followed by environmental conditions, while age was not significant and gender showed a small effect. Conclusions. Study habits in higher education are better explained by the combined contribution of motivational and contextual factors than by static sociodemographic characteristics. Motivation guides academic engagement, while environmental conditions facilitate its stabilization in consistent study routines.